1965
DOI: 10.1002/macp.1965.020860120
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl polymerization. 93. Polar effects in radical polymerization of p‐substituted styrenes

Abstract: The radical polymerization of styrene and of the p-substituted styrenes p-methoxy-, p-methyl-, p-fluoro-, p-chloro-, p-bromo-, and p-cyanostyrene, was kinetically studied. The styrenes with more electron-attracting substituents show a greater overall rate of polymerization. At 30,O "C., the individual rate constants of propagation (kp) and termination (kt) were determined by a rotating sector and by usual inhibitor method using diphenylpicrylhydrazyl (DPPH) or p-benzoquinone. It was found that the following HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
4

Year Published

1980
1980
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 14 publications
(6 reference statements)
4
29
4
Order By: Relevance
“…and k~ of this system equal those of substituted polystyryl radicals, 16 Tables II and III. K~/k~ are calculated based on eq 10 using the experimental data of Rx/RH and k!/k~, 16 and k~/k~ are used the experimental data, RY/RH_ In the case of styrenes, k~/ k~ decreased in the order ofMeO, Me, and then Cl. k~/~ ofthiophenols increased in the order of OH, MeO, Me, and Cl.…”
Section: Relative Rates Of Adduct Formationmentioning
confidence: 96%
“…and k~ of this system equal those of substituted polystyryl radicals, 16 Tables II and III. K~/k~ are calculated based on eq 10 using the experimental data of Rx/RH and k!/k~, 16 and k~/k~ are used the experimental data, RY/RH_ In the case of styrenes, k~/ k~ decreased in the order ofMeO, Me, and then Cl. k~/~ ofthiophenols increased in the order of OH, MeO, Me, and Cl.…”
Section: Relative Rates Of Adduct Formationmentioning
confidence: 96%
“…But, absolute p values of TBA system are about twice those of the TP system. Imoto et al 22 claim that p changed greatly by the polarity of the attacking radical controlled by the substituent in the addition reactions of various polystyryl radicals to substituted styrenes. It was also found in the present system that the electrophilicity of the benzoylthiyl radical was larger than that of the benzenethiyl radical to St or EB.…”
Section: Substituent Effect On the Addition Stepmentioning
confidence: 99%
“…15,18,19 Kinetic studies on substituted styrenes have shown that a linear correlation can be obtained between the apparent rate coefficient, k p app ϭ Ϫ d(ln [M])/ dt, and the Hammett constant, , for various substituents, with a slope ϭ 1.5 for atom transfer radical polymerization (ATRP), 20 ϭ 1.45 for TEMPO-mediated polymerization, 16 and ϭ 0.6 for conventional free-radical polymerizations. 21 From these results ( controlled Ͼ conventional ), it was deduced that the larger k p app for electronwithdrawing substituents (EW; e.g., for CMS in comparison with styrene) would be caused not only by a larger k p but also by a larger equilibrium constant, K eq , between propagating and dormant polymer chains and/or a larger [Cu I ]/[Cu II ] ratio (in copper-mediated ATRP; i.e., a larger [P-T]/[T*] ratio in nitroxide-mediated polymerizations). Georges et al 16 estimated that the increase in K eq ϭ k d /k c should mainly be due to a decrease in k c , whereas k d would be relatively independent of the substituents.…”
Section: Introductionmentioning
confidence: 99%